Otimização do sistema de tratamento composto por reator eletroquímico seguido por flotação por ar dissolvido: aplicação em efluente de frigorífigo e matadouro de suínos - Bocchi, Ruan (2022)
An activity with significant economic importance for Brazil is the animal slaughter industry and meat processing. However, this sector is responsible for the generation of waste on a large scale, with wastewater presenting high concentrations of organic matter. The treatment of this effluent is required to provide the correct disposal, or even its reuse. The use of combined technologies in the treatment of effluents can be an attractive option to achieve treatment efficiency associated with resource savings. Thus, the objective of this work was to evaluate the performance of electrocoagulation in a cylindrical batch reactor followed by dissolved air flotation in the treatment of effluents from a swine slaughterhouse and slaughterhouse. Through a Central Composite Rotational Design (CCRD) it was possible to evaluate the effects of electrolysis time and electric current density for the electrocoagulation step and saturation pressure and hydraulic retention time for the dissolved air flotation step. The results obtained with the tests carried out indicate that the electrocoagulation process was promising for the removal of COD, turbidity and color in effluent from a refrigerator and swine slaughterhouse, with efficient results for the removal of such parameters (efficiency greater than 80%). Regarding the energy consumption in the electrocoagulation stage, it was observed that it was high, where for each (m3) of effluent from the refrigerator and slaughterhouse of treated swine, an energy consumption that varied in the range of 447.20 was spent. at 2060.97 Wh.m-3. Regarding the residual aluminum concentration, a variation from 13.2 to 34.2 mg.L-1 was observed in the electrocoagulation stage when analyzing the treated effluent. As for the dissolved air flotation stage, the results showed an improvement in the quality of the effluent from the swine slaughterhouse and slaughterhouse and acted as a complement to the electrocoagulation treatment, increasing the efficiency of 93% for color and turbidity removal and 78 % for COD removal.